Medically important biofilms and non-thermal plasma - Julák, Jaroslav; Scholtz, Vladimír; Vaňková, Eva (World journal of microbiology & biotechnology, 2018)
In recent decades, the non-thermal plasma, i.e. partially or completely ionized gas produced by electric discharges at ambient temperature, has become of interest for its microbiocidal properties with potential of use in the food industry or medicine. Recently, this interest focuses not only on the planktonic forms of microorganisms but also on their biofilms. The works in this interdisciplinary field are summarized in this review. The wide range of biofilm-plasma interactions is divided into studies of general plasma action on bacteria, on biofilm and on its oral and dental application; a short overview of plasma instrumentation is also included. In addition, not only biofilm combating but also an important area of biofilm prevention is discussed. Various DC discharges of the point-to-plane type. Author's photograph, published in Khun et al. (Plasma Sources Sci Technol 27:065002, 2018).
Keywords: Fungi; Wound healing; Biofilm inactivation; Bacteria; houby; Food Industry; potravinářský průmysl; Dental and oral; Non-thermal plasma production; zubní materiály; Wound Healing; Biofilms; Disinfection; dezinfekce; biofilmy; plazmové plyny; Dental Materials; Biofilm prevention; Plasma Gases; hojení ran